Pengaruh Sistem Tirani Dalam Kepemimpinan terhadap Kinerja dan Loyalitas Anggota : Kepercayaan pada Pemimpin Sebagai Variabel Intervening - Irwan Tahir; Suriyanti, Suriyanti; Serlin Serang (Al-Buhuts, 2025)
This study aims to analyze the direct  effects  of  Tyrannical  Leadership  on  Leader  Trust,  Performance,  and  Loyalty,  as  well  as evaluate the mediating role of Leader Trust. A quantitative approach was employed, with a population consisting of Polri members and a sample selected through purposive sampling. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The findings revealed that Tyrannical Leadership had no significant effect on Leader Trust and Loyalty but had a small significant effect  on  Performance.  In contrast, Leader Trust  had  a significant  and  strong influence on both Performance and Loyalty. These results highlight the importance of trust as a key element in enhancing subordinate performance and loyalty, while also demonstrating that tyrannical leadership is less effective in fostering productive working relationships. This study recommends Polri to adopt a trust-based leadership style focused on transparent communication, consistency, and the creation of a fair and supportive work environment